1985
DOI: 10.1037/0735-7036.99.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Social dynamics of group courtship behavior in male red-sided garter snakes (Thamnophis sirtalis parietalis).

Abstract: Mating in red-sided garter snakes is characterized by the formation of mating balls. Up to 100 males simultaneously court single females. The social dynamics of the formation of these mating balls was examined to determine whether the mating balls are formed simply because of a common attraction to the female or whether males are stimulated by the mating balls themselves. A sexually attractive female garter snake appears to be even more attractive to a male when she is being courted by other males than when sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 15 publications
1
33
1
Order By: Relevance
“…Similar results have been reported in most previous studies of the same species, with large females attracting more suitors than small females (Aleksiuk & Gregory, 1974;Hawley & Aleksiuk, 1976;Gartska et al, 1982;Shine et al, 2001b). Only one previous study of red-sided garter snakes has reported that female body size did not in uence courtship intensity (Joy & Crews, 1985). Large females stimulate higher tongue-ick rates from mate-searching male snakes (Shine et al, 2003c).…”
Section: Female Body Sizesupporting
confidence: 84%
See 2 more Smart Citations
“…Similar results have been reported in most previous studies of the same species, with large females attracting more suitors than small females (Aleksiuk & Gregory, 1974;Hawley & Aleksiuk, 1976;Gartska et al, 1982;Shine et al, 2001b). Only one previous study of red-sided garter snakes has reported that female body size did not in uence courtship intensity (Joy & Crews, 1985). Large females stimulate higher tongue-ick rates from mate-searching male snakes (Shine et al, 2003c).…”
Section: Female Body Sizesupporting
confidence: 84%
“…4c) and heavier-bodied males performed more frequent caudocephalic waves (Table 1). An earlier study of the same population reported a similar result, with more active courtship by large males (Joy & Crews, 1985). Extensive data from eld and arena matings have shown that larger, heavier-bodied males experience higher mating success than do their small, thinner rivals (Shine et al, 2000f).…”
Section: Male Body Size and Body Conditionmentioning
confidence: 68%
See 1 more Smart Citation
“…Courting wild males (N10) were then placed into each arena, and the proportion of males courting the experimental male was recorded after 10min by an observer who was blind to the experimental treatments. Previous work has shown that male redsided garter snakes exhibit facilitated courtship, where larger groups of competing males induce more vigorous, reliable male courtship behavior in arena trials than assays using single males paired with a female (Joy and Crews, 1985). Courting males were distinguished by conspicuous chin-rubbing behavior where the male tongue-flicks the dorsal surface of the female and aligns his body with hers, a behavior seen only in the reproductive context [see Moore et al (Moore et al, 2000) and for recent ethograms describing male red-sided garter snake reproductive behavior].…”
Section: Behavioral Testsmentioning
confidence: 99%
“…Males were randomly selected from both treatment groups and introduced in groups of eight to simulate natural mating conditions, where the presence of a mating ball facilitates male courtship behavior (Joy and Crews, 1985). Mating balls rarely contain fewer than five males courting a single female because males are attracted to females by both the presence of pheromonal cues expressed on the female's dorsal surface as well as the presence of a mating ball (Joy and Crews, 1985).…”
Section: Reproductive Behaviormentioning
confidence: 99%